PENGGUNAAN PAKAN NON KONVENSIONAL TERFERMENTASI DALAM RANSUM TERHADAP NILAI ORGANOLEPTIK DAGING AYAM BROILER: THE USE OF FERMENTED NON-CONVENTIONAL FEED IN RATIONS ON THE ORGANOLEPTICAL VALUE OF BROILER MEAT - Anggraeni; Elis Dihansih; Deden Sudrajat; Renaldi, Aldi (Jurnal Peternakan Nusantara, 2023)
This study aims to determine the effect of non-conventional fermented feed substitution in rations on the sensory properties of broiler chicken meat. It was held from May to June 2017 which was located in the poultry pens of the Department of Animal Husbandry, Juanda University, Bogor. Tests for proximate analysis of palm kernel meal, coconut meal, tofu dregs, and cassava were carried out at the Laboratory of the Center for Biological Resources and Biotechnology Research, Bogor Agricultural University, while the sensory test for broiler chicken meat was carried out at the Sartika Laboratory, Djuanda University, Bogor. This study used 24 chickens. The research design used was a completely randomized design with 6 treatments and 4 replications. The feed used consists of R0 = 100% basic feed, R1 = 90% basic feed + 10% fermented non-conventional feed, R2 = 75% basic feed + 25% fermented non-conventional feed, R3 = 60% basic ration + 40% unconventional fermented feed, R4 = 45% basic feed + 55% fermented non-conventional feed, R5 = 30% basic feed + 70% non-conventional feed. Meat samples were taken from the breast to test the sensory quality of the meat. The variables observed were the sensory properties of the meat consisting of aroma, color, tenderness, taste and juiceness. The organoleptic assessment was carried out by hedonic test and hedonic quality, the assessment was carried out by 25 semi-trained panelists. Based on the results of the study that substitution of basic feed with fermented non-conventional feed in rations on consumption acceptability including aroma, taste, tenderness, juiceness and texture can maintain the sensory quality of broiler chicken meat.